IMPLEMENTATION OF MANAGEMENT IN WASTE BANKS TO INCREASE ECONOMIC VALUE - Fahmi Fauziah; Andi Hamzah; Ahmad Rozy (Jurnal PKM Manajemen Bisnis, 2021)
Waste waste is one of the most crucial environmental problems, but some people have been able to take advantage of this as household income. Among other things, waste is processed into fertilizer, processed into magot feed, and some types of waste with higher economic value can be sold directly (iron, paper, plastic). Due to the attractiveness of the use of this waste, especially in it there is economic value, it is fitting that waste be managed with management science. This is intended so that all waste management activities can be recorded, and important information is obtained about the revenue from waste management, so that management activities and their income can be better controlled. This activity is carried out at the Pamulang landfill, which can accommodate between 1 ton and 2 tonnes of waste every day. Based on the results of the activity, it was known that this knowledge-sharing activity was very well responded to by the participants, and even the participants felt happy because they had been given knowledge, which was directly related to their activities, especially in generating income.